PERAN FILSAFAT ISLAM DALAM MEMBANGUN TRADISI KEILMUAN - Husain Heriyanto (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2014)
Treasures of classical and contemporary Islamic philosophy is very rich indeed. Unfortunately, until now this intellectualproperty is still stored in the libraries. The Avicennas thought as a genius philosopher, for instance, was notexplored all, especially the eventual development of such thinking in Tanbht wa al-Manthiq al-Masyriqiyyah (EastLogic). Not many people know how Ibn Sina solved the problems of scientific and philosophical methods are alsothrough meditation and prayer, long before Quantum Learning was excited. The specificity of Islamic philosophy is acomprehensive and integrated way to study the metaphysics, epistemology, ethics, cosmology, and psychology. In thispaper the authors highlight how the role of philosophy in building a scientific tradition. Science that not only develop theadvancement of science alone, but also spawned generations aware of his existence and humanity.